Channel trajectories control deep‐water stratigraphic architecture. (22nd April 2022) - Morris, Paul D.; Sylvester, Zoltán; Covault, Jacob A.; Mohrig, David
Abstract: Interpretation of deep‐water channel deposits is challenging because the spatial arrangement of their constituent lithologies is highly variable. This variability is often thought to be a signature of complex interactions between controlling boundary conditions and processes. A three‐dimensional forward stratigraphic model of a sinuous meandering channel is used to explore the production of channelised deep‐water stratigraphy. This model highlights three stages of stratigraphic evolution for channel belts: (1) an initial phase of rapid growth in mean belt width and variability in belt width driven by increasing channel sinuosity; (2) a subsequent phase of reduced belt‐width growth rate because of cutoff processes; and (3) a mature phase during which repeated bend lifecycles act to produce a statistically stable channel‐belt width. When a trajectory defining the vertical movement of a channel over time is added to the model, commonly recognised patterns of deep‐water channel‐belt stratigraphy are produced. These results demonstrate how forward stratigraphic models provide insights into processes governing the evolution of deep‐water stratigraphy that elude interpretations of static outcrops and seismic images of subsurface examples. Abstract : We use a forward stratigraphic model based on a sinuous meandering channel to highlight three stages of stratigraphic evolution for channel belts: 1) an initial phase of rapid growth in mean belt width and variability in belt width driven by increasing channel sinuosity; 2) a subsequent phase of reduced belt‐width growth rate because of cutoff processes; and 3) a mature phase during which repeated bend lifecycles act to produce a statistically stable channel‐belt width. When a trajectory defining the vertical movement of a channel over time is added to the model, commonly recognised patterns of deep‐water channel‐belt stratigraphy are produced.